Gums induced microstructure stability in Ca(II)-alginate beads containing lactase analyzed by SAXS - Traffano Schiffo, Maria Victoria (2018)
Previous works show that the addition of trehalose and gums in β-galactosidase (lactase) Ca(II)-alginate encapsulation systems improved its intrinsic stability against freezing and dehydration processes in the pristine state. However, there is no available information on the evolution in microstructure due to the constraints imposed by the operational conditions. The aim of this research is to study the time course of microstructural changes of Ca(II)-alginate matrices driven by the presence of trehalose, arabic and guar gums as excipients and to discuss how these changes influence the diffusional transport (assessed by LF-NMR) and the enzymatic activity of the encapsulated lactase. The structural modifications at different scales were assessed by SAXS. The incorporation of gums as second excipients induces a significant stabilization in the microstructure not only at the rod scale, but also in the characteristic size and density of alginate dimers (basic units of construction of rods) and the degree of interconnection of rods at a larger scale, improving the performance in terms of lactase activity.